2022
DOI: 10.7759/cureus.25540
|View full text |Cite
|
Sign up to set email alerts
|

Differences of Lipid Profile Among Ischemic and Hemorrhagic Stroke Patients in a Tertiary Hospital in Riyadh, Saudi Arabia: A Retrospective Cohort Study

Abstract: Objective This study aims to compare the serum lipid profiles of patients with ischaemic and hemorrhagic strokes. Study design This was a retrospective, comparative study. Place and duration of the study The study was conducted at Military Hospital, Riyadh, from January 1, 2018, to December 31, 2020. Methodology Patients with a diagnosis of stroke who presented to the emergency department and was confirmed to have ischemic or hemorrha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…On the other hand, our study demonstrated no significant difference between the ischemic and hemorrhagic stroke groups in the serum values of other lipid components (LDL-C, HDL-C, TG). This finding agrees with previous studies that found no statistical significance in the serum values of TG and LDL-C between ischemic and hemorrhagic stroke, although there were a significantly lower HDL-C levels in the former than the latter [ 54 , 61 ]. However, numerous studies have found significant variations in such lipid components with stroke type [ 58 , [62] , [63] , [64] ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, our study demonstrated no significant difference between the ischemic and hemorrhagic stroke groups in the serum values of other lipid components (LDL-C, HDL-C, TG). This finding agrees with previous studies that found no statistical significance in the serum values of TG and LDL-C between ischemic and hemorrhagic stroke, although there were a significantly lower HDL-C levels in the former than the latter [ 54 , 61 ]. However, numerous studies have found significant variations in such lipid components with stroke type [ 58 , [62] , [63] , [64] ].…”
Section: Discussionsupporting
confidence: 93%
“…In contrary, an inverse relationship between TC and hemorrhagic stroke has been observed in other studies [ [56] , [57] , [58] ]. In several other reports, TC was not identified to be associated or showed only weak relationships with types of stroke [ 52 , [59] , [60] , [61] ].…”
Section: Discussionmentioning
confidence: 84%
“…In our study, the average TLC was 9.9X109/L, the average RNC was 67.7%, the average TC was 174 mg/dL, the average TG was 144.4 mg/dL, the average LDL was 101 mg/dL, the average HDL was 44.4 mg/dL, the average bilirubin was 1.1 mg/dL, the average direct bilirubin was 0.2 mg/dL, the average ALT was 18.5 U/ While Alkhaneen et al found that the fasting serum lipid profile of 114 ischemic stroke patients revealed elevated serum total cholesterol in 23.7% of patients, with a mean serum total cholesterol of 4.3 mmol/L, we found that the proportion of patients with elevated serum total cholesterol was significantly lower. 32 For patients with follow-up, the Modified Rankin Scale (mRS) revealed that 32.4% had no major impairment, 41.2% had little disability, 7.4% had moderate disability, 11.8% had moderately severe disability, and 7.4% had passed away. All patients were divided into two groups: those with favourable outcomes (mRS scores 2) and those with unfavourable outcomes (mRS scores 3).…”
Section: Discussionmentioning
confidence: 99%
“…According to some studies, a significant portion of stroke patients have aberrant lipid profiles, with differences between ischemic and hemorrhagic strokes noted. 12 The association between cholesterol and stroke, particularly hemorrhagic stroke, presents an inverse relationship, distinct from the direct link seen in coronary heart disease. Understanding these distinctions is crucial to tailoring lipid-lowering therapies effectively, potentially reducing stroke incidence and related mortality rates.…”
Section: Introductionmentioning
confidence: 99%